Anticipations and Purchases : An Analysis of Consumer Behavior - Juster, F. Thomas (Francis Thomas), 1926- (Book collections on Project MUSE., 2015)
The author is concerned with whether or not surveys of consumer anticipations can improve predictions of purchase behavior relative to predictions that use only objective variables obtainable at the same date. The basic objective of the study is improved predictions of changes over time.Originally published in 1964.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.